2019
DOI: 10.1111/gcb.14915
|View full text |Cite
|
Sign up to set email alerts
|

Introduced plants as novel Anthropocene habitats for insects

Abstract: Major environmental changes in the history of life on Earth have given rise to novel habitats, which gradually accumulate species. Human‐induced change is no exception, yet the rules governing species accumulation in anthropogenic habitats are not fully developed. Here we propose that nonnative plants introduced to Great Britain may function as analogues of novel anthropogenic habitats for insects and mites, analysing a combination of local‐scale experimental plot data and geographic‐scale data contained withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 81 publications
1
9
0
Order By: Relevance
“…While we have emphasized the critical role of indigenous plants, we have also shown that indigenous insects are being found in association with a wide array of regionally native and nonnative plants. Thus, our study supports the idea that urban environments facilitate novel resource utilization by indigenous insects (Padovani et al 2020, Valentine et al 2020). Future experimental work on this topic is needed to clarify to what extent these associations reflect host shifting patterns unique to urban environments and to fully understand the opportunities and risks provided by novel urban resources.…”
Section: Discussionsupporting
confidence: 90%
“…While we have emphasized the critical role of indigenous plants, we have also shown that indigenous insects are being found in association with a wide array of regionally native and nonnative plants. Thus, our study supports the idea that urban environments facilitate novel resource utilization by indigenous insects (Padovani et al 2020, Valentine et al 2020). Future experimental work on this topic is needed to clarify to what extent these associations reflect host shifting patterns unique to urban environments and to fully understand the opportunities and risks provided by novel urban resources.…”
Section: Discussionsupporting
confidence: 90%
“…Novel ecosystems are on the rise, in large part driven by introductions of non‐native species, but also promoted by ongoing global warming, increased atmospheric carbon dioxide (CO 2 ) and land use change (Feng et al., 2014; Hobbs et al., 2009; Perring & Ellis, 2013). The new species assemblages and ecosystem functions of these novel ecosystems are likely to alter ecosystem services (Collier, 2014; Evers et al., 2018; Hobbs et al., 2009; Millenium Ecosystem Assessment, 2005) may threaten native species (Bellard, Genovesi, & Jeschke, 2016; Pyšek et al., 2012) but could also generate new habitats for native species (Padovani, Salisbury, Bostock, Roy, & Thomas, 2020). An improved understanding of the functioning of novel ecosystems to these increasingly widespread natural environments should clearly be an important research priority (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In both studies, nonnative plants also hosted significantly lower abundances of invertebrates in addition to an overall lower diversity (Burghardt and Tallamy 2015, Padovani et al. 2020). Other studies have similarly found that invertebrates linked to nonnative plants typically are generalists rather than specialists (Brändle et al.…”
Section: Introductionmentioning
confidence: 96%
“…In general, the time since introduction of a new plant species has been found to be positively correlated to the arthropod abundance and diversity that it hosts, meaning that nonnative plants introduced earlier support higher insect abundance than more recent introductions (Br€ andle et al 2008, Padovani et al 2020. Furthermore, nonnative plants closely related to local species (congeneric species) generally host more invertebrates both in terms of abundance and diversity compared to less closely related nonnatives (Burghardt et al 2010, Burghardt and Tallamy 2015, Padovani et al 2020. This suggest that the difference in invertebrate abundance and diversity hosted by nonnative and native vegetation can be explained by a lack of coevolutionary history, which shapes relations between many pollinators and herbivores and their host plants (Ehrlich and Raven 1964).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation